A PRELIMINARY STUDY ON DESIGNED STRATEGY TO IMPROVE EMPLOYEES’ PERFORMANCE WITH CONSIDERATION TO THE EMPLOYEES’ CAREER DEVELOPMENT - Wagimin Wagimin; Winda Nur Cahyo (Center for Study and Journal Management FTI UMI, 2021)
This research is intended to test the effect of career development on work motivation, auditor certification and job performance with work motivation and auditor being the moderator variables. The number of respondents involved in this research was 222 individuals. All the respondents are employees of PT BKI Kalimantan Timur. This research is done using the quantitative approach. The type of data used is primary data obtained by the distribution of questionnaire. The questionnaire was analyzed using the Partial Least Square technique with the use of SmartPLS program. Based on the analytic results of this research it can be concluded that there is a significant proof that there are positive effects on work motivation, auditor certification and auditor’s performance. A good career development programme can increase work motivation, supports the auditor certification and improve on job performance of auditors. The result of this study also proves that a good work motivation and auditor certification strengthen the effect of career development on auditor job performance